PENGARUH MOTIVASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA FAVE HOTEL KUTA BALI - I Made Dedi Adi Pratama; I Ketut Sutapa (Journal Research of Management, 2021)
This research is behind the phenomena of motivation and physical work environment that are still lacking in Fave Hotel Kuta Bali. physical. which is still not conducive to be considered as an inhibiting factor in improving employee performance This study aims to analyze and prove the influence of motivation and physical work environment on employee performance. This research uses a descriptive method with a quantitative approach. The sample technique used is the nonprobability sampling technique, which is saturated sampling. The number of respondents who used 75 Fave Hotel Kuta employees. Multiple linear regression analysis using SPSS software version 23. Regression equation obtained: Y = 0.570-0.302X1 + 0.268X2. The results of this study indicate that; First, motivation has a positive influence on employee performance at Fave Hotel Kuta. Second, the physical work environment has a positive effect on employee performance at Fave Hotel Kuta. Third, the magnitude of the influence contributed by motivation and physical work environment on employee performance at Fave Hotel Kuta is 57.0% Some suggestions that can be conveyed from this study include; the absence of a better future guarantee from fave hotel kuta by some employees as well as from indicators of social needs namely lack of interaction between employees at work, lighting indicators can be overcome by moving the lights in strategic places and not blinding the eyes